Seismotectonics of Mongolia and Baikal Rift Zone Controlled by Lithospheric Structures - Huang, Zhouchuan; Zhao, Dapeng (Geophysical research letters, 2022)
Active tectonics are developing in Mongolia and the Baikal rift zone, where large crustal earthquakes (Mw ≥ 6.0) occur frequently. To clarify the mechanism of these earthquakes, we determine a high‐resolution 3‐D P‐wave velocity model of the crust and upper mantle beneath Mongolia and the Baikal rift zone. We find an annular high‐velocity zone in the lithosphere; whereas low‐velocity anomalies exist both inside and around the high‐velocity ring as well as beneath the rift zone. Strong interactions between the high‐velocity ring and the surrounding terranes may have induced many moderate‐to‐large earthquakes (Mw 5–7). By contrast, mega‐earthquakes (Mw ≥ 8.0) occurred right above the high‐velocity ring. We propose that the high‐velocity ring is strong as a whole; it sustains the stress arising from the India‐Asia collision and causes the mega‐earthquakes. Meanwhile, the ring could protect the Hangay Dome from the regional compression, leading to weak seismicity under the dome. Plain Language Summary Mongolia and the Baikal rift zone are regions with heavy intracontinental seismic hazards. Three mega‐earthquakes (Mw ≥ 8.0) and more than 30 large earthquakes (Mw ≥ 6.0) have occurred there since 1900. In this work we determined a new 3‐D velocity model of the crust and upper mantle under this region. Comparison of the structural heterogeneities and earthquake locations suggests that the earthquake generation is controlled by the lithospheric structures, especially the three mega‐earthquakes took place above a high‐velocity ring in the upper mantle around the Hangay Dome. The high‐velocity ring may prevent the dome from stress accumulation so that the dome is free of earthquake damage although it is weak. Key Points Seismic tomography reveals a high‐velocity ring in the crust and upper mantle beneath Mongolia and Baikal rift zone Moderate‐to‐large earthquakes (Mw 5–7) occurred above low‐velocity zones among different blocks Mega‐earthquakes (M ≥ 8.0) occurred above a high‐velocity ring which sustains the distant effect of the Indo‐Asian collision